2013
DOI: 10.1007/s11420-013-9331-2
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography during Cardiac Arrest in Orthopedic Surgery Patients: A Report of Two Cases and a Review of the Literature

Abstract: Background: Cardiac arrest situations represent an enormous clinical challenge to the physicians involved. Research suggests that the utilization on transesophageal echocardiography (TEE) may provide important diagnostic information and allows for institution of more specific treatment, while not hampering resuscitation efforts. Case Description: In this review, we highlight the usefulness of TEE in cardiac arrest situations in the orthopedic setting, by presenting two perioperative cases. In one case, TEE was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Orthopedic and trauma patients are some of those at highest risk for thrombi, but cardiac anesthesiologists are seldom found administering these anesthetics. Although right ventricular strain is the most common finding in these cases, our patient showed a global deterioration [ 9 ]. One explanation is that the patient's extensive fracture resulted in occult bleeding which contributed to severe hemodynamic instability and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Orthopedic and trauma patients are some of those at highest risk for thrombi, but cardiac anesthesiologists are seldom found administering these anesthetics. Although right ventricular strain is the most common finding in these cases, our patient showed a global deterioration [ 9 ]. One explanation is that the patient's extensive fracture resulted in occult bleeding which contributed to severe hemodynamic instability and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative TEE is extremely useful for monitoring and diagnosis. One study discovered that in 19 out of 22 cardiac arrests, TEE was successful in establishing a diagnosis [ 9 ]. In addition, TEE provides a survival benefit, allowing clot visualization and initiation of specific treatment plans [ 2 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, no study has assessed the impact of TOE on survival. [19][20][21][22] There are similar data from observational studies performed mostly in emergency settings regarding the value of echocardiography for diagnosis of the cause of cardiac arrest but not for improving outcomes. 23 One systematic review suggested that the absence of spontaneous cardiac motion seen with TOE in patients with a a low probability for ROSC may predict a low likelihood of survival as well as guide CPR decisions, but the clinical settings of the included studies were outside of the operating room.…”
Section: Identification Of Cardiac Arrestmentioning
confidence: 97%
“…TEE for noncardiac surgical procedures is frequently used in cases such as liver transplantation, but also in cases with specific cardiac risks or in patient populations with significant cardiac comorbidities. Additionally, TEE may be used in situations when previously unrecognized cardiac conditions exist or in high-risk procedures to help guide resuscitative measures [4]. Because many life-threatening conditions (such as pericardial effusion or air embolism, for example) can be recognized in a more efficient manner by using TEE, those who have obtained basic certification should be able to recognize such conditions [5 && ].…”
Section: Echocardiography Certificationmentioning
confidence: 99%